The Effect of Physical Exercise on Promoting the Mental Health Level of English Teachers - Si Chen (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
In order to better understand the mental health level of English teachers, the author proposes a study on the effect of physical exercise on promoting the mental health level of English teachers.The author takes English teachers in a certain province as the research object to analyze and demonstrate the impact of physical exercise on the mental health status and level of health of English teachers. Using the "Symptom Checklist for Mental Health (SCL-90)" questionnaire and the physical exercise participation survey questionnaire, the SCL-90 psychological scale consists of 10 factors: Somatization, depression, compulsion, interpersonal sensitivity, anxiety and hostility, terror, paranoia, mental illness, and others. A random questionnaire was distributed to English teachers in the province, with a total of 200 questionnaires distributed, 190 questionnaires collected, and 185 valid questionnaires. The job of an English teacher involves intense mental labor, and prolonged and high-intensity work can lead to fatigue and irritability, leading to a decrease in mental health levels. Teachers who frequently participate in physical exercise have better mental health levels than those who do not frequently participate in physical exercise and those who never participate in physical exercise, teachers who participate in collective project exercise and those who participate in individual forms of physical exercise have certain differences in factors such as depression, anxiety, hostility, and paranoia. Education management departments should pay more attention to the psychological health of teachers, regularly provide psychological counseling to English teachers, and their units should regularly organize physical activities for teachers to mobilize everyone to participate in physical exercise, continuously improve teachers' mental health level through physical exercise.